Effectiveness of delayed-release dimethyl fumarate on patient-reported outcomes and clinical measures in patients with relapsing–remitting multiple sclerosis in a real-world clinical setting: PROTEC. Issue 4 (December 2019) - Berger, T; Brochet, B; Brambilla, L; Giacomini, PS; Montalbán, X; Vasco Salgado, A; Su, R; Bretagne, A
Background: Patient-reported outcomes (PRO) and clinical outcomes give a broad assessment of relapsing–remitting multiple sclerosis (RRMS) disease. Objective: The aim is to evaluate the effectiveness of delayed-release dimethyl fumarate (DMF) on disease activity and PROs in patients with RRMS in the clinic. Methods: PROTEC, a phase 4, open-label, 12-month observational study, assessed annualized relapse rate (ARR), proportion of patients relapsed, and changes in PROs. Newly diagnosed and early MS (≤3.5 EDSS and ≤1 relapse in the prior year) patient subgroups were evaluated. Results: Unadjusted ARR at 12 months post-DMF versus 12 months before DMF initiation was 75% lower (0.161 vs. 0.643, p  < 0.0001) overall ( n  = 1105) and 84%, 77%, and 71% lower in newly diagnosed, ≤3.5 EDSS, and ≤1 relapse subgroups, respectively. Overall, 88% of patients were relapse-free 12 months after DMF initiation (84%, newly diagnosed; 88%, ≤3.5 EDSS; 88%, ≤1 relapse). PRO measures for fatigue, treatment satisfaction, daily living, and work improved significantly over 12 months of DMF versus baseline. Conclusion: At 12 months after versus 12 months before DMF initiation, ARR was significantly lower, the majority of patients were relapse-free, and multiple PRO measures showed improvement (overall and for subgroups), suggesting that DMF is effective based on clinical outcomes and from a patient perspective. Clinical trial: A Study Evaluating the Effectiveness of Tecfidera (Dimethyl Fumarate) on Multiple Sclerosis (MS) Disease Activity and Patient-Reported Outcomes (PROTEC), NCT01930708, https://clinicaltrials.gov/ct2/show/NCT01930708 .